Socio Cultural Study of Temanggung Tobacco Farmers In the Global Trans Era - Ali Imron; Muhammad Niky Nur Komaruddin; Eri Setyo Darmawan; Novita Ayu Kurnia Illahi (CV. Literasi Indonesia, 2020)
Temanggung is one of the biggest tobacco producers in Indonesia. So far, tobacco has only been understood from an economic perspective. Though there are cultural aspects that also accompany it. Planting tobacco for the community is not only sowing seeds, but also a matter of noble culture. One of them is tobacco farmers in Legoksari Village. This research aimed to describe the cultural process in tobacco farming in Legoksari Village. This research used a qualitative method with ethnographic approach. The data analysis technique used was the Spradley model with domain, componential, taxonomic, and theme analysis. The results of this research indicated that in tobacco farming in Legosari Village there are four cultural rituals from the beginning of planting to harvest. Starting from Nyecel, Among Tebal, Lekas ​​Tebal, and Miwiti. Including the initial planting period using the Pranoto Mongso calendar. Planting tobacco also pays attention to siti, wiji, wanci, and perati. This showed that tobacco farming in Temanggung is full of cultural noble values.